Chemokine signaling is required for homeostatic and injury‐induced neurogenesis in the olfactory epithelium. (25th January 2021) - Senf, Katja; Karius, Julia; Stumm, Ralf; Neuhaus, Eva M.
Abstract: The olfactory epithelium (OE) possesses unique lifelong neuroregenerative capacities and undergoes constitutive neurogenesis throughout mammalian lifespan. Two populations of stem cells, frequently dividing globose basal cells (GBCs) and quiescent horizontal basal cells (HBCs), readily replace olfactory neurons throughout lifetime. Although lineage commitment and neuronal differentiation of stem cells has already been described in terms of transcription factor expression, little is known about external factors balancing between differentiation and self‐renewal. We show here that expression of the CXC‐motif chemokine receptor 4 (CXCR4) distinguishes both types of stem cells. Extensive colocalization analysis revealed exclusive expression of CXCR4 in proliferating GBCs and their neuronal progenies. Moreover, only neuronal lineage cells were derived from CXCR4‐CreER‐tdTomato reporter mice in the OE. Furthermore, Cre‐tdTomato mice specific for HBCs (Nestin+ and Cytokeratin14+) did not reduce CXCR4 expression when bred to mice bearing floxed CXCR4 alleles, and did not show labeling of the neuronal cells. CXCR4 and its ligand CXCL12 were markedly upregulated upon induction of GBC proliferation during injury‐induced regeneration. in vivo overexpression of CXCL12 did downregulate CXCR4 levels, which results in reduced GBC maintenance and neuronal differentiation. We proved that these effects were caused by CXCR4 downregulation rather than over‐activation by showing that the phenotypes of CXCL12‐overexpressing mice were highly similar to the phenotypes of CXCR4 knockout mice. Our results demonstrate functional CXCR4 signaling in GBCs regulates cell cycle exit and neural differentiation. We propose that CXCR4/CXCL12 signaling is an essential regulator of olfactory neurogenesis and provide new insights into the dynamics of neurogenesis in the OE. Abstract : CXCL12 is secreted by cells of the lamina propria and activates the chemokine receptor CXCR4 in globose basal cells of the olfactory epithelium. Receptor activation promotes division of these stem cells, and thereby regulates the size of the stem cell pool. Absence of CXCR4 signaling leads to exit from the cell cycle and increased neuronal differentiation.